South Africa's Financial Sector Charter : transforming South Africa through black economic empowerment - Rosenthal, Jean W., 1945- (SAGE knowledge. Cases., 2016)
In 1994, South Africa held its first free elections, marking the peaceful transition from a government controlled by the country's white minority to a multi-party, multi-racial government. The new government, led by Nelson Mandela and the African National Congress (ANC) party, sought to unify South Africa and overcome the country's racist past. Rather than pursue criminal recriminations and retribution for past wrongs, the ANC concentrated on reconciliation, unification and nation building. According to most observers, the ANC's political program led to a strong, forward-looking state, capable of undertaking the significant challenges facing South Africa. This case study examines this topic.